2022
DOI: 10.1088/1742-6596/2219/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

GLSTM-DTA: Application of Prediction Improvement Model Based on GNN and LSTM

Abstract: Most prediction models of drug-target binding affinity (DTA) treated drugs and targets as sequences, and feature extraction networks could not sufficiently extract features. Inspired by DeepDTA and GraphDTA, we proposed an improved model named GLSTM-DTA for DTA prediction, which combined Graph Neural Network (GNN) and Long Short-Term Memory Network (LSTM). The feature extraction block consists of two parts: GNN block and LSTM block, which extract drug features and protein features respectively. The novelty of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This model extended the time-dependent extension of the graph learning model. Hybrid models based on graph learning have been applied in many fields, such as biology [41], pharmacy [42], network interconnection [43], etc.…”
Section: Related Workmentioning
confidence: 99%
“…This model extended the time-dependent extension of the graph learning model. Hybrid models based on graph learning have been applied in many fields, such as biology [41], pharmacy [42], network interconnection [43], etc.…”
Section: Related Workmentioning
confidence: 99%
“…Compared with the traditional LSTM method, Bi-LSTM improves prediction accuracy. In addition, LSTM also has a good performance on time-based case analysis, they proposed the GLSTM-DTA for DTA prediction, which combined graph neural network (GNN) with LSTM to extract drug features and protein features, which is facilitating to capture of long-term dependencies in sequence [24]. In addition, the Graph LSTM addresses the limitations of sequential models, and also help to utilize the semantic correlation between cases and categories on the temporal [25].…”
Section: Time-series Geographic Information Analysismentioning
confidence: 99%
“…Theoretically, when GNNs are combined with gated recurrent units (GRUs), the GNN captures the feature relationships between nodes 5 , while the GRU captures the temporal dependencies of these features. Recent studies have reported using GNN-GRU models for spatiotemporal traffic flow prediction 6 .…”
Section: Introductionmentioning
confidence: 99%